Improved accuracy of etiological diagnosis of spinal infection by metagenomic next-generation sequencing - Xu, Liang; Zhou, Zheng; Wang, Yao; Song, Chao; Tan, Hongdong (Frontiers in Cellular and Infection Microbiology, 2022)
Currently, the use of metagenomic next-generation sequencing (mNGS), a new approach to identify organisms in infectious diseases, is rarely reported in the diagnosis of spinal infection. This study aimed to evaluate the potential value of mNGS in etiological diagnosis of spinal infection. In this retrospective study, the clinical data of patients with suspected spinal infection were collected by electronic medical records. Specimens obtained from each patient were tested via mNGS assay and other conventional microbiological tests (CMTs). The sensitivity and specificity of mNGS and CMTs were calculated using the final clinical diagnosis as the golden standard. In total, 108 patients were eligible for the study, with the mean length of stay of 42.8 days. Regarding the overall identification of pathogens, mNGS exhibited a better performance than CMTs, and several nontuberculous mycobacteria, fungi, and bacteria were newly discovered. In the diagnosis of spinal infection, the sensitivity, specificity, and area under the curve of mNGS were 90.72%, 81.82%, and 0.89, respectively, which were all higher than 52.17%, 56.25%, and 0.72 of the CMTs. At hospital discharge, the C-reactive protein, erythrocyte sedimentation rate, and white blood cell count of patients significantly decreased compared with hospitalization (all p < 0.05), and 88.89% showed good outcomes. These findings may suggest that mNGS has a better diagnostic accuracy in pathogenic identification of patients with suspected spinal infection, and patients treated with NGS-guided antimicrobial therapy mostly seem to have good outcomes.